Effects of Gladiolus dalenii on the Stress-Induced Behavioral, Neurochemical, and Reproductive Changes in Rats - Fotsing, David; Ngoupaye, Gwladys T.; Ouafo, Agnes C.; Njapdounke, Stephanie K. J.; Kenneth, Yongabi A.; Ngo Bum, Elisabeth (Frontiers in Pharmacology, 2017)
Gladiolus dalenii is a plant commonly used in many regions of Cameroon as a cure for various diseases like headaches, epilepsy, schizophrenia and mood disorders. Recent studies have revealed that the aqueous extract of G. dalenii exhibited antidepressant-like properties in rats. Therefore we hypothesized that the aqueous extract of Gladiolus dalenii could protect from the stress-induced behavioral, neurochemical, and reproductive changes in rats. The objective of the present study was to elucidate the effect of the aqueous extract of Gladiolus dalenii (AEGD) on behavioral, neurochemical and reproductive characteristics, using female rats subjected to chronic immobilization stress. The chronic immobilization stress (3hours per day for 28 days) was applied to induce female reproductive and behavioral impairments in rats. The immobilization stress was provoked in rats by putting them separately inside cylindrical restrainers with ventilated doors at ambient temperature. The plant extract was given to rats orally everyday during 28 days, 5 minutes before induction of stress. On a daily basis, a vaginal smear was made to assess the duration of the different phases of the estrous cycle and at the end of the 28 days of chronic immobilization stress, the rat’s behavior was assessed in the elevated plus maze. They were sacrificed by cervical disruption. The organs were weighed, the ovary histology done and the biochemical parameters assessed. The findings of this research revealed that G. dalenii increased the entries and the time of open arm exploration in the elevated plus maze. Evaluation of the biochemical parameters levels indicated that there was a significant reduction in the corticosterone, progesterone and prolactin levels in the G. dalenii aqueous extract treated rats compared to stressed rats whereas the levels of serotonin, triglycerides, adrenaline, cholesterol, glucose estradiol, follicle stimulating hormone (FSH) and luteinizing hormone (LH) were significantly increased in the stressed rats treated with, G. dalenii, diazepam and in co-administration of the plant extract and diazepam treated rats. Moreover stressed rats showed significant changes in estrous cycle phases compared to vehicle control and these changes of the estrous cycle were less in the rats treated with G. dalenii compared to the negative control rats.